Processamento e caracterização da blenda poli (metacrilato de metila) (PMMA) elastomerico e poli (tereftalato de etileno) (PET) pós-consumo - Reinaldo, Juciklécia da Silva (2013)
This work studied the immiscible blend of elastomeric poly(methyl methacrylate) (PMMA) with poly(ethylene terephthalate) (PET) bottle grade with and without the use of compatibilizer agent, poly(methyl methacrylate-co-glycidyl methacrylate - co-ethyl acrylate) (MGE). The characterizations of torque rheometry, melt flow index measurement (MFI), measuring the density and the degree of cristallinity by pycnometry, tensile testing, method of work essential fracture (EWF), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were performed in pure polymer and blends PMMA/PET. The rheological results showed evidence of signs of chemical reaction between the epoxy group MGE with the end groups of the PET chains and also to the elastomeric phase of PMMA. The increase in the concentration of PET reduced torque and adding MGE increased the torque of the blend of PMMA/PET. The results of the MFI also show that elastomeric PMMA showed lower flow and thus higher viscosity than PET. In the results of picnometry observed that increasing the percentage of PET resulted in an increase in density and degree crystallinity of the blends PMMA/PET. The tensile test showed that increasing the percentage of PET resulted in an increase in ultimate strength and elastic modulus and decrease in elongation at break. However, in the phase inversion, where the blend showed evidence of a co-continuous morphology and also, with 30% PET dispersed phase and compatibilized with 5% MGE, there were significant results elongation at break compared to elastomeric PMMA. The applicability of the method of essential work of fracture was shown to be possible for most formulations. And it was observed that with increasing elastomeric PMMA in the formulations of the blends there was an improvement in specific amounts of essential work of fracture (We) and a decrease in the values of specific non-essential work of fracture (βWp)